Correction: Praeruptorin B improves diet-induced hyperlipidemia and alleviates insulin resistance via regulating SREBP signaling pathway. Issue 11 (19th February 2019) - Zheng, Zu-Guo; Lu, Chong; Thu, Pyone Myat; Zhang, Xin; Li, Hui-Jun; Li, Ping; Xu, Xiaojun
Abstract : Correction for 'Praeruptorin B improves diet-induced hyperlipidemia and alleviates insulin resistance via regulating SREBP signaling pathway' by Zu-Guo Zheng et al., RSC Adv., 2018, 8, 354–366.